A new genus and species of the tribe Trigonogeniini Cobos, 1956, from Belize (Coleoptera: Buprestidae) - Bílý, Svatopluk (Zootaxa, 2009)
The name Trigonogenium Harold, 1869 was introduced as a replacement name for Trigonophorus Solier, 1849 (preoccupied by Serville,1834: Hymenoptera). The genus was revised by Cobos (1956) who discussed the systematic position of Trigonogenium and suggested for the genus a separate tribe Trigonogenini (sic !). The next revision was published also by Cobos (1986) and the placement of the genus was repeatedly discussed by Hołyński (1988, 1993), Bílý (2000), Volkovitsh (2001), Bellamy (2003, 2007) and the tribal level of the group was finaly confirmed by Bílý & Volkovitsh (2007) after a detailed study of the larval morphology. Up to now the tribe has contained only two genera: Trigonogenium (three species and one subspecies) and Hovorigenium Bellamy, 2007 (one species).